Arthroscopic Single-Tunnel Pullout Suture Fixation for Tibial Eminence Avulsion Fracture - Elsaid, Ahmed Nady Saleh (Arthrosc Tech, 2018)
Various arthroscopic techniques have been devised for fixation of tibial eminence avulsions, namely percutaneous K-wires, arthroscopy-guided screw fixation, staples, TightRope (Arthrex)–suture button fixation, and transosseous suture fixation. Such techniques provide well-pronounced advantages including less postoperative pain, a reduced hospital stay, and minimal scar with resultant earlier and more compliant rehabilitation. As for transosseous suture fixation, the standard technique comprises the creation of 2 tibial tunnels exiting on both sides of the footprint of the avulsion fracture using an anterior cruciate ligament tibial guide with the angle set at 45°. Our technique entails the creation of a single tibial tunnel directed from the proximal anteromedial tibia to the center of the tibial eminence. The technique uses Ethibond suture (No. 5) and/or FiberWire suture (Arthrex) to fix the tibial eminence by pulling the anterior cruciate ligament fibers and tightening the pullout suture at the tibial exit of the tunnel with a 4-hole button. This modified single-tunnel pullout suture technique is an appealing option that has proved to be effective and economical with a shorter operative time. Moreover, it provides a less invasive option for skeletally immature patients.